Assessment Method of Multipath Mitigation Performance for GNSS Antenna with Receiver Algorithms. (18th September 2017) - Yuan, Muzi; Li, Du; Li, Baiyu; Chen, Huaming; Ou, Gang
Abstract : Multipath is one of the most important sources of positioning error in GNSS. Well-designed antennas can mitigate multipath signals and enhance the performance of GNSS receivers. This paper concentrates on methods to assess multipath mitigation performance for GNSS antennas. We propose a model to describe multipath environment in GNSS ground stations. The model analyzes effects caused by inclined reflective surfaces and multipath mitigating algorithms in receivers. A method to assess multipath mitigation performance is put forward by analyzing pseudorange code phase errors caused by multipath signals after signal processing. Based on the model and method, principles in site selection for GNSS antenna are introduced to minimize effects caused by multipath.